Modeling the improved textural properties of purple waxy rice dried through fluidization. Issue 9 (4th July 2018) - Rattanamechaiskul, Chaiwat; Junka, Nittaya; Prachayawarakorn, Somkiat; Soponronnarit, Somchart
ABSTRACT: This study developed a mathematical model and gelatinization kinetic equation for drying rice through fluidization. This model was then applied to improve the softness and stickiness of non-milled waxy rice (NWR) to be comparable to those of milled waxy rice (MWR). The results demonstrate that the hardness value decreased and that the stickiness value increased with an increasing degree of starch gelatinization. The model and equation were validated based on their satisfactory R 2 values and were then used to predict the suitable degree of starch gelatinization and to recommend drying conditions. Compared to MWR, the simulated NWR had an equal hardness value and a larger stickiness value.